The Prognostic Value of Androgen Receptor Splice Variant 7 in Castration-Resistant Prostate Cancer Treated With Novel Hormonal Therapy or Chemotherapy: A Systematic Review and Meta-analysis - Zhize Wang; Haixiang Shen; Nieying Ma; Qinchen Li; Yeqing Mao; Chaojun Wang; Liping Xie (Frontiers in Oncology, 2020)
PurposeThis study aimed to evaluate the prognostic role of AR-V7 in terms of prostate-specific antigen (PSA) response, progression-free survival (PFS), and overall survival (OS) in CRPC patients treated with novel hormonal therapy (NHT) (Abiraterone and Enzalutamide) or taxane-based chemotherapy (Docetaxel and Cabazitaxel).MethodsA comprehensive literature search was conducted on PubMed, Embase, and the Web of Science from inception to February 2020. Studies focusing on the prognostic values of AR-V7 in CRPC patients treated with NHT or chemotherapy were included in our meta-analysis. The OS and PFS were analyzed based on Hazard ratios (HRs) and 95% confidence intervals (CIs). Furthermore, Odds ratios (ORs) and 95% CIs were summarized for the AR-V7 conversion after treatment and the PSA response.ResultsThe AR-V7 positive proportion increased significantly after NHT treatment (OR 2.56, 95% CI 1.51–4.32, P<0.001), however, it declined after chemotherapy (OR 0.51, 95% CI 0.28–0.93, P=0.003). AR-V7-positive patients showed a significantly decreased PSA response rate after NHT (OR 0.13, 95% CI 0.09–0.19, P<0.001) but not statistically significant for chemotherapy (OR 0.63, 95% CI 0.40-1.01, P=0.06). Notably, PFS (HR 3.56, 95% CI 2.53–5.01, P<0.001) and OS (HR 4.47, 95% CI 3.03–6.59, P<0.001) were worse in AR-V7-positive ttreated with NHT. Similarly, AR-V7 positivity correlated with poor prognosis after chemotherapy as evidenced by shorter OS (HR 1.98, 95% CI 1.48-2.66, P<0.001) and a significantly shorter PFS (HR 1.35, 95% CI 0.97-1.87, P=0.07).ConclusionNHT treatment increased AR-V7 positive proportion whereas chemotherapy decreased it. Moreover, AR-V7 positivity correlated with lower PSA response, poorer PFS, and OS in CRPC treated with NHT, and shorter OS in patients receiving chemotherapy.